BjSP, a novel serine protease from Bothrops jararaca snake venom that degrades fibrinogen without forming fibrin clots - Carone, Sante E.I.; Menaldo, Danilo L.; Sartim, Marco A.; Bernardes, Carolina P.; Caetano, Renato C.; da Silva, Ronivaldo R. [UNESP]; Cabral, Hamilton; Barraviera, Benedito [UNESP]; Ferreira Junior, Rui S. [UNESP]; Sampaio, Suely V. (Elsevier, 2018)
Snake venom serine proteases (SVSPs) are commonly described as capable of affecting hemostasis by interacting with several coagulation system components. In this study, we describe the isolation and characterization of BjSP from Bothrops jararaca snake venom, a serine protease with distinctive properties. This enzyme was isolated by three consecutive chromatographic steps and showed acidic character (pI 4.4), molecular mass of 28 kDa and N-carbohydrate content around 10%. Its partial amino acid sequence presented 100% identity to a serine protease cDNA clone previously identified from B. jararaca venom gland, but not yet isolated or characterized. BjSP was significantly inhibited by specific serine protease inhibitors and showed high stability at different pH values and temperatures. The enzyme displayed no effects on washed platelets, but was able to degrade fibrin clots in vitro and also the Aα and Bβ chains of fibrinogen differently from thrombin, forming additional fibrinopeptides derived from the Bβ chain, which should be related to its inability to coagulate fibrinogen solutions or platelet-poor plasma. In the mapping of catalytic subsites, the protease showed high hydrolytic specificity for tyrosine, especially in subsite S1. Additionally, its amidolytic activity on different chromogenic substrates suggests possible effects on other factors of the coagulation cascade. In conclusion, BjSP is a serine protease that acts nonspecifically on fibrinogen, generating different Bβ fibrinopeptides and thus not forming fibrin clots. Its distinguished properties in comparison to most SVSPs stimulate further studies in an attempt to validate its potential as a defibrinogenating agent.
Keywords: Bothrops jararaca; Coagulation; Fibrinogen; Serine protease; Snake venom